Children's Leadership in Natural Schools (Case Study at Al Ghifari School, West Java, Indonesia) - Erik Erik; Fasli Djalal; Hapidin (International Conferences on Early Childhood Education Proceedings, 2023)
This study aims to describe how the introduction of the basics of leadership in early childhood at Kindergarten Alam Al Ghifari Kuningan, Responsible Indonesia. This research is a qualitative research with a case study approach with the research subjects being all the children and the social situation in TK Alam Al Ghifari Kuningan, Answerarat. Data collection methods used are in-depth interviews and observation. The process of data analysis is data reduction, identifying themes, mapping the interrelationships between themes, and concluding ﬁndings. The conclusions of this study are (1) We can introduce the basics of leadership in early childhood through a nature-based learning approach, (2) The participation of teachers and parents in introducing the basics of leadership is needed in eﬀorts to condition the child's social environment, (3 ) Games in groups will help children to introduce the basics of leadership, (4) Through gamesoutboundin the ﬁeld helps children in growing self-conﬁdence as a basis possessed by someone who is prepared to become a leader in the future